2013
DOI: 10.1179/1476830512y.0000000028
|View full text |Cite
|
Sign up to set email alerts
|

A study of neurobehavioral, clinical psychometric, and P3 changes in vitamin B12 deficiency neurological syndrome

Abstract: VBDNS results in frontal-subcortical neurobehavioral and cognitive abnormalities which may be due to cortical and subcortical dysfunction. The reversibility of these changes is suggestive of metabolic alteration in neuronal or myelin function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…The neurophysiologic evaluation of our participants also included QST and SSEPs, but no changes were observed in these variables after the vitamin B-12 injection, possibly because an improvement in vitamin B-12 status affects mainly large afferent peripheral nerves rather than the smaller fibers. Similar improvements in peripheral sensory conduction velocity were described in vitamin B-12-deficient patients with clinical symptoms by Kalita et al (30), although they also showed an increase in the amplitude of the motor compound action potential. Tredici et al (31), in an experimental model of vitamin B-12 deficiency in rats, described intramyelinic and interstitial edema without axonal damage associated with a reduction of nerve conduction velocity.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The neurophysiologic evaluation of our participants also included QST and SSEPs, but no changes were observed in these variables after the vitamin B-12 injection, possibly because an improvement in vitamin B-12 status affects mainly large afferent peripheral nerves rather than the smaller fibers. Similar improvements in peripheral sensory conduction velocity were described in vitamin B-12-deficient patients with clinical symptoms by Kalita et al (30), although they also showed an increase in the amplitude of the motor compound action potential. Tredici et al (31), in an experimental model of vitamin B-12 deficiency in rats, described intramyelinic and interstitial edema without axonal damage associated with a reduction of nerve conduction velocity.…”
Section: Discussionsupporting
confidence: 62%
“…Tredici et al (31), in an experimental model of vitamin B-12 deficiency in rats, described intramyelinic and interstitial edema without axonal damage associated with a reduction of nerve conduction velocity. Only at a more-advanced stage, when the abnormalities are clinically expressed, would the peripheral sensory neuropathy express as axonal (6,16,30). The fact that we detected changes in peripheral but not central nerve conduction suggests that sensory peripheral nerve conductivity is the most-useful method for the assessment of subclinical neurologic effects of vitamin B-12 deficiency and repletion.…”
Section: Discussionmentioning
confidence: 76%
“…Other authors have also reported visual-evoked potential abnormality in up to 70% (9) and sensory-evoked potential abnormality up to 100% of patients (10). Cognitiveevoked potential was abnormal in 58% patients with VBDNS and improved after therapy (2). The improvement in evoked potentials suggests an important role of vitamin B-12 in myelin functions.…”
mentioning
confidence: 88%
“…The frequency of neuropsychiatric and cognitive abnormalities in vitamin B-12 deficiency depends on the extent of evaluation. In one study, 42% of patients with vitamin B-12 deficiency neurological syndrome (VBDNS) had abnormalities on neuropsychiatric inventory; these included anxiety, apathy, aggression, irritability, hallucinations, delusions, and disinhibition, in descending order (2). In another study of VBDNS (3), myelopathy was present in 93% of patients, cognitive impairment in 48%, and neuropathy in 44%.…”
mentioning
confidence: 98%
See 1 more Smart Citation